Endocrine therapy for early breast cancer. Issue 5 (1st October 2004) - Hussain, Syed A; Williams, Sarah; Stevens, Andrea; Rea, Daniel W
Breast cancer is a significant cause of morbidity and mortality. Adjuvant tamoxifen therapy for estrogen receptor-positive early breast cancer has had a major impact on mortality in clinical trials, and the observation that breast cancer mortality started to decline shortly after widespread tamoxifen prescription was introduced in several countries inevitably leads us to conclude that this intervention is responsible. Aromatase inhibitor therapy will undoubtedly become part of everyday practice in the future, although the optimization of aromatase inhibitor therapy as part of the overall endocrine package needs further definition. However, to suppose that a unified optimal sequence and duration is applicable to all patients is probably a fallacy, and underlying the overall effects of different treatments are individual patients with individual but potentially classifiable tumors requiring different management strategies. Characterization and individualization of therapies based on gene and proteomic expression profiling is a massive research undertaking, but could guide us towards a fairly simple set of key gene or protein expression profiles to guide adjuvant hormonal, chemotherapeutic or new biologic agent strategies that will define optimal treatment packages for women with early breast cancer. Within the next 5 years, the clinical reservations regarding adjuvant aromatase inhibitors and financial obstacles to access the aromatase inhibitors are likely to be overcome and, unless we are able to identify a cohort of women who will gain no additional benefit or who have a better outcome with tamoxifen, most postmenopausal women will be treated with aromatase inhibitor monotherapy or a sequential combination utilizing an aromatase inhibitor.